The future of organic farming – reflections on the new legislation - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2020)
The purpose of the considerations is, taking into account the scope of derogations from the requirements of organic production and the competence of certifying authorities, to answer the question whether in comparison to Regulation No 834/2007, new Regulation No 2018/848 serves to ensure the quality of organic products. The authoress takes a positive view on limiting possible exemptions from the requirements of organic production to natural disasters and linking them to the provisions on rural development. At the same time she expresses a negative opinion on the possibility of seeking exemption from the requirement to obtain certificates. In relation to the competences of the certifying authorities, the new Regulation retains a greater terminological precision in determining the subject of control and certification and defines more precisely the criteria for delegating tasks in the organic farming control system to institutions. This issue, however, needs to be detailed in the legislations of European Union Member States.